Promoter Specificity and Biological Activity of Tethered AP-1 Dimers - Bakiri, Latifa (American Society for Microbiology, 2002)
Activator protein 1 (AP-1) is a group of dimeric transcription factors composed of Jun, Fos, and ATF family proteins. Both gain- and loss-of-function studies have revealed specific roles for individual AP-1 components in cell proliferation, differentiation, apoptosis, and other biological processes. However, little is known about the functions of specific AP-1 dimers. To test the importance of AP-1 composition in transcriptional activation, AP-1 monomers were joined via a flexible polypeptide tether to force specific pairing. The resultant single-chain AP-1 molecules showed DNA binding specificity and transcriptional activation potentials similar to those of untethered dimers, even in the presence of dominant-negative AP-1 monomers. c-Jun-containing dimers showed distinct promoter specificity in transient-transfection experiments, depending on the Fos, Fra, or ATF partner. When stably expressed in NIH 3T3 cells, c-Jun∼Fra2, but not c-Jun∼Fra1 and c-Jun∼cFos (the tilde indicates a tethered dimer), inhibited G(0) arrest at confluency and under low-serum conditions and specifically activated cyclin A expression. These data suggest that the choice of dimerization partner defines the role of c-Jun in gene activation and cell cycle regulation and that single-chain AP-1 molecules provide a powerful tool for assessing the role of specific AP-1 dimers.